Blueprint badbug zapper / Izzati Ahmad Radzi...[et al.] - Ahmad Radzi, Izzati; Abang Hipni, Dayang Irzah Shazwani; Noryazid, Nur Athirah; Fadzil, Nurul Farhana
Badbug Zapper is a product which is best described as a portable insect slayer with style without sacrificing any safety features. The product also acts as an insect control. Insects will be attracted to the light source which is lid up by using batteries. The light source which attracts insects will enhance insects towards the electrical caging where they are electrocuted when their body makes contact with the wires, consisting of two high voltage levels between them. This product also comes with other unique features such as air freshener, alarm clock and rechargeable battery. These unique features can be use simultaneously while the insects are being attracted.The target market for this product would be the people of all ages especially the teenagers, adults and senior citizen. Our initial target is to market our product in Giant Hypermarket all around Malaysia and we wish to expand our business to the international market.